Representing ‘Native Speakers’ on English Language Teaching (ELT) Websites in China - Qin, Lanqing (Université d'Ottawa | University of Ottawa, 2024)
The ‘native speaker’ has been haunting the ELT profession for a long time. As I describe in my literature review, many recent debates about this term have revolved around problematic political meanings and effects derived from Chomsky’s construct of the ‘ideal monolingual native speaker.’ It persists in our field and continues to exert materialized impacts on both ‘non-native’ and ‘native’ professionals. My study is contributing to a group of critical scholarship which dismantle the stability of the ‘native speaker.’ Drawing on the theoretical framework of poststructuralism, particularly through the perspective of representation (Hall, 1997), my study examined the ways in which ‘native speakers’ were represented on a purposeful sample of ELT websites in contemporary China, where English education has been a significant part of the country’s modernization project. Through a critical discourse analysis of 8 ELT websites filtered from a corpus of 34 websites, I have worked to deconstruct the formation process of the category of ‘native speakers’ and reveal the power relations at work. I have looked at the “languages,” such as texts, images, linguistic uses, videos and physicality, being employed by these websites, which indicated to the audience who a ‘native speaker’ is and what they looked like. My analysis suggested that overall, the ELT websites saturated the term ‘native speaker’ with a hegemonic representation of young, gorgeous White English teachers of European and North American origins who speak in either British or American accent. These ‘native speakers’ were perceived to embody a certain way of thinking and performing the English language and represented a posh and fancy global world outside China. I showed that, at times, White male bodies were exploited as commodities to sell to students and projected with a hint of Occidental romanticism. I argue that Whiteness and accent are complexly entangled issues which have significant implications for understanding the native speaker construct in contemporary China, and that beyond this the websites are articulating the cultural hegemony of the English language. My analysis also shed light on a group of Filipino ‘non-native speaking’ English teachers represented as legitimate ELT professionals, which countered the White dominance and challenged the absolute authority of ‘native speakers’ as the ideal of English language teaching. My study calls for critical attention to the craze for standard accent in ELT and the British/American cultural hegemony behind this craze, as well as to the connection between Whiteness and the English language.
Keywords: native speakers; English language teaching (ELT); Whiteness; representation; China; deconstruction